Early Interview of Speech Delay with Phonics Method in Children with Speech Delay Age 3 Years at Graha Husada Hospital Gresik - Rachmatus Salsabilah; Prianggi Amelasasih (Indonesian Vocational Research Journal, 2023)
Language disorders are delays in the language sector experienced by a child. A child can be said to have a delay in speaking if the child's level of speech development is below the level of quality of normal child's speech development in general according to his age, this can be seen from the correct use of words. The subject in this study with the initials MDE is 3 years old, this patient underwent routine therapy as much as twice a week. According to therapists who treat MDE, MDE is a child who has speech delay. The following are the results of researchers' observations of MDE who have speech delay. In this research, the phonics method is used, where the phonics method is "a method of teaching reading that is related to sound". Where these letters consist of vowels and consonants which are combined into syllables and sentences. This research uses experimental research methods, experimental research consists of pre-test and post-test. The post test showed an increase in the subject, on the first day the subject got a score of 8, on the second day 14, on the third day 16, and on the fourth day 18, where this score showed an increase. In conclusion, this phonics method is functional and can be used on research subjects of children aged 3 years.